2024
DOI: 10.1161/atvbaha.123.319663
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase SHP2 in Macrophages Acts as an Antiatherosclerotic Regulator in Mice

Chenxia Wu,
Peiyao Zheng,
Lan Ma
et al.

Abstract: Background: Macrophages have versatile roles in atherosclerosis. SHP2 (Src homology 2 containing protein tyrosine phosphatase 2) has been demonstrated to play a critical role in regulating macrophage activation. However, the mechanism of SHP2 regulation of macrophage function in an atherosclerotic microenvironment remains unknown. Methods: APOE (apolipoprotein E) or low-density lipoprotein receptor null mice treated with SHP099 were fed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…170 Presently, several inhibitors have been developed, among which JAB-3068, BBP-398, and RMC-4630 have entered clinical trials. 171 In addition, the role of SHP2 in macrophages and fibroblasts has been studied, 196,197 and it may be essential for vascular development. Lately, Xu et al demonstrated that SHP2 expression is upregulated in TECs, and it promotes angiogenesis as well as vessel defects through the SHP2-ASK1-c-Jun-SOX7 axis, which may benefit tumor growth.…”
Section: Key Genes Regulating Endothelial Cellsmentioning
confidence: 99%
“…170 Presently, several inhibitors have been developed, among which JAB-3068, BBP-398, and RMC-4630 have entered clinical trials. 171 In addition, the role of SHP2 in macrophages and fibroblasts has been studied, 196,197 and it may be essential for vascular development. Lately, Xu et al demonstrated that SHP2 expression is upregulated in TECs, and it promotes angiogenesis as well as vessel defects through the SHP2-ASK1-c-Jun-SOX7 axis, which may benefit tumor growth.…”
Section: Key Genes Regulating Endothelial Cellsmentioning
confidence: 99%